A longitudinal workforce analysis of a Rural Clinical Placement Program for final year dental students. (22nd April 2019) - Johnson, G; Byun, R; Foster, K; Wright, FAC; Blinkhorn, A
Abstract: Background: There is little longitudinal evaluation of rural dental education outreach programs. This longitudinal research investigates the influence of a Rural Clinical Placement Program (RCPP) on workforce outcomes in terms of practice locations for five graduate years from the University of Sydney. Methods: Work locations for the graduates from 2009–2013 were identified in 2015 and 2017 by rurality, using faculty contact lists, phone calls and online methods. A total of 397 graduate locations were identified out of 404 (98.2%) (267 RCPP participants and 137 non‐RCPP participants). Semi‐structured questionnaires were used to report on demographic and characteristic data. Univariate and multivariate statistical analyses were utilised to explore associations. Results: Rural Clinical Placement Program participation in 2015 was significantly associated with an increased likelihood of working rurally (PR = 2.16), and almost two times the likelihood of rural retention in the period from 2015 to 2017 (PR = 1.93). In the multivariate analyses, both rural experience prior to the RCPP and pre‐placement rural intentions were significant independent predictors of an increased likelihood for rural employment and rural retention. Conclusions: Participation in the RCPP was associated with increased rural employment and retention. Prior rural experience and pre‐placement rural intentions were identified as significant independent predictors of rural employment.